EFFECT OF MOISTURE CONTENT LEVELS ON SOME ENGINEERING PROPERTIES OF LOCUST BEAN (PARKIA BIGLOBOSA) SEEDS (2012)
Locust bean (Parkia biglobosa) seed is a source of a nutritious and medicinal food condiment consumed in Nigeria. The drudgery associated with locust bean seed processing necessitates its mechanization. However, there is a dearth of information on the engineering properties of locust bean required for machine design. Since water absorption by seeds causes changes in their structure and size, this study was designed to investigate some engineering properties of locust bean at different moisture content levels. Locust bean pods were collected from Araromi, Saki in Oyo State. The moisture content and physical properties were determined using American Society of Agricultural Engineers' (S 352.2), Mohsenin's (1986) and Stepanoff's (1969) methods. Universal testing machine was used to determine the mechanical properties. Force was applied transversely at 5 mm/min loading rate. Normal and shear stresses were determined for 200 - 500 g loads at 100 g interval. Thermal properties were determined using methods of mixture and steady-state heat of vaporization. Data were analysed using ANOVA. Seed length, width and surface area increased from 10.2±1.0 to 11.3±0.9 mm, 8.5±0.8 to 9.1±0.6 mm, and 191.2±24.6 to 208.3±26.3 mm2 respectively. Static and dynamic angles of repose increased from 48.4±0.9 to 56.0o ±1.4 and 25.2±1.5 to 30o ±1.2 respectively as seed moisture content increased from 5.9 to 28.2 % d.b. Seeds became sticky and clung together at high moisture content, hindering free flow and piling at rest, and increased angle of repose. Static coefficient of friction increased on plywood (0.48±0.02 to 0.60±0.01), glass (0.40±0.05 to 0.54±0.01), mild-steel (0.52±0.04 to 0.54±0.02), galvanized iron (0.51±0.04 to 0.52±0.03), rubber (0.41±0.04 to 0.60±0.05) and decreased on aluminium (0.54±0.02 to 0.52±0.04) and stainless steel (0.55±0.03 to 0.50±0.04). The increase was due to increased adhesion between the seeds and the test surfaces at high moisture levels while surface smoothness reduced adhesion, accounting for the decrease in static friction on aluminium and stainless steel. Seed thickness, sphericity and rupture force decreased from 5.49±0.43 to 5.26±0.62 mm, 0.75±0.04 to 0.71±0.03 and 214.4±82.3 to 129.9±51.9 N respectively while normal stress increased with increase in moisture content and loads; 8.4 to 8.7 gcm-2 for 200 g, 9.4 to 9.7 gcm-2 for 300 g, 10.4 to 10.7 gcm-2 for 400 g and 11.4 to 11.7 gcm-2 for 500 g. Shear stress was highest at 11.11 % moisture d.b. under 500 g load (1.5 gcm-2) and lowest at 5.93 % moisture d.b. under 200 g load (0.6 gcm-2). Increase in stresses was due to reduced porosity within the grain bulk at high moisture content. Thermal diffusivity, specific heat capacity and thermal conductivity increased from 2.93 x 10-8 to 3.79 x 10-8 m2/s, 2.74 to 4.38 kJ/kg oC and 0.052 to 0.118 W/m oC respectively, these showed that seeds were able to transmit and retain heat within the grain bulk at high moisture content. A baseline data of the engineering properties of locust bean seeds useful for design of necessary equipment have been established. The properties are useful in designing flat storage facilities and steamers.